IL‐7 germline variant: setting the stage for immune‐related adverse events - Hussein Issaoui; Jean‐Ehrland Ricci (Molecular Oncology, 2023)
Treatment with immune checkpoint inhibitors (ICIs) is frequently associated with immune‐related adverse events (irAEs). A new study identified an interleukin 7 (IL‐7) allelic variant—rs16906115—as a major risk factor for the development of ICI‐associated irAEs. This association is of great significance as it indicates that germline genetic variants influence the occurrence of irAEs, thus opening a new avenue for identifying high‐risk patients to enable better management of ICI therapy and associated irAEs.